Llamas - Buller, Laura, 1952- (New York, New York : DK Publishing, 2019)
Read about the lives of long-necked llamas! Why do llamas spit? What's the difference between a llama and an alpaca? Find out everything you need to know about this amazing animal.
Llama life -- What are llamas like? -- Home of the llamas -- The Incas -- A helpful animal -- The family tree -- Llama friends -- Smile if you love llamas -- Quiz --Glossary -- Index.
Includes index.
107906
Keywords: Llamas -- Juvenile literature; Instructional and educational works; Juvenile works; Picture books; Readers (Publications)